Development of environmentally sensitive fluorescent and dual emissive deoxyuridine analogues1. Issue 42 (10th May 2015) - Barthes, N. P. F.; Karpenko, I. A.; Dziuba, D.; Spadafora, M.; Auffret, J.; Demchenko, A. P.; Mély, Y.; Benhida, R.; Michel, B. Y.; Burger, A.
<x xml:space="preserve">Abstract</x> We designed and developed fluorescent deoxyuridine analogues with strong sensitivity to hydration for the major groove labelling of DNA.